Application of Media Combination of PhET Simulation and Spring Balance on Mathematical Concept Understanding of Grade XI Students on Vector Material - Khofifah Khofifah; Atin Supriatin; Jhelang Annovasho (Universitas Lambung Mangkurat, 2024)
This study aims to determine the improvement in mathematical concept understanding of grade XI students after applying the combined media of PhET simulation and spring balance to vector material. The type of research used (pre-experimental) using a one-group pretest-posttest design. The sampling technique used is purposive sampling, namely 30 class XI MIPA 1 MAN Kota Palangka Raya students. Concept understanding data were analyzed using descriptive and inferential methods. Based on data analysis, it was found that the average pretest score was 23.4 while the post-test was 87.5. The t-test results show that ????-count = -39.594 < ????-???????????????????? = 3.39624. Thus, it can be concluded that HO is rejected and HA is accepted, so there is a significant increase in the understanding of mathematical concepts of class XI students on vector material before and after applying to learn using a combination of PhET simulation media and spring balance. The implication of using the media is that it provides significant benefits in understanding mathematical concepts, skill development, and student engagement in learning so that students are more focused and learning becomes directed.